2020
DOI: 10.5194/acp-20-16007-2020
|View full text |Cite
|
Sign up to set email alerts
|

North Atlantic marine organic aerosol characterized by novel offline thermal desorption mass spectrometry: polysaccharides, recalcitrant material, and secondary organics

Abstract: Abstract. The composition of organic compounds in marine aerosols and the relative contributions of primary and secondary organic compounds remain uncertain. We report results from a novel approach to characterize and quantify organic components of the marine aerosol. Size-segregated discrete aerosol filter samples were collected at sea in the North Atlantic from both ambient aerosol and artificially generated primary sea spray over four cruises timed to capture the seasonal phytoplankton bloom dynamics. Sampl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 52 publications
2
25
1
Order By: Relevance
“…Microorganisms become embedded and enriched within a gel matrix of polymeric surfactants in the SML (Aller et al, 2005;Thornton et al, 2016), such as transparent exopolymer particles (TEP) (Alldredge et al, 1993) and Coomassie staining particles (CSP) (Long and Azam, 1996). This is consistent with the identification of polysaccharides in marine aerosol from the North Atlantic Ocean (Aller et al, 2017;Lawler et al, 2020). It has been presumed that the SML plays a dominant role in determining the composition of the organic matter is SSA.…”
Section: Generation Of Marine Aerosolsupporting
confidence: 53%
See 3 more Smart Citations
“…Microorganisms become embedded and enriched within a gel matrix of polymeric surfactants in the SML (Aller et al, 2005;Thornton et al, 2016), such as transparent exopolymer particles (TEP) (Alldredge et al, 1993) and Coomassie staining particles (CSP) (Long and Azam, 1996). This is consistent with the identification of polysaccharides in marine aerosol from the North Atlantic Ocean (Aller et al, 2017;Lawler et al, 2020). It has been presumed that the SML plays a dominant role in determining the composition of the organic matter is SSA.…”
Section: Generation Of Marine Aerosolsupporting
confidence: 53%
“…Therefore, it is likely that nascent SSA generally contains a complex mixture of DOM from labile to ultra-recalcitrant. Chemical characterization of samples from the North Atlantic by Lawler et al (2020) supports this hypothesis. Lawler et al (2020) concluded that there was a seasonal signal associated with labile polysaccharides and a relatively constant pool of recalcitrant organic matter associated with alcohol groups.…”
Section: Organic Matter Contributions To Primary Marine Aerosolmentioning
confidence: 63%
See 2 more Smart Citations
“…The composition of submicron primary marine aerosol varied with season and latitude (Lewis et al). Organic materials in aerosol were linked to ubiquitous recalcitrant dissolved organic matter and transient polysaccharides emitted under bloom conditions (Lawler et al, 2020).…”
Section: Aerosols Sourced From the Oceanmentioning
confidence: 99%